Formulation and Statistical Evaluation of Tablets Containing Pitavastatin- Self Nano Emulsifying Drug Delivery Systems - Gowripattapu, Sridevi; Sathis Kumar, D.; Selvamuthukumar, S. (Current Drug Delivery, 2023)
Purpose: To formulate and characterize tablets containing Pitavastatin that have been loaded with a self-nano emulsifying drug delivery system (SNEDDS). Methods: Pitavastatin SNEDDS were prepared with a variety of oils, surfactants, co-surfactants, and solvents to improve the dissolution rate and bioavailability of the HMG-CoA reductase inhibitor. The SNEDDS components were preliminarily investigated for drug solubility in various vehicles, excipient miscibility, emulsification rate, and ternary phase diagrams. The tablets were made using a porous carrier made of Aerosil 200 and then loaded with SNEDDS using a simple absorption method. Physical parameters such as tablet hardness, weight variation, disintegration, drug content, and in-vitro drug release were then measured on the tablets. Results: Labrafac Lipophilewl1349 (Oil), Tween 80 (Surfactant) and Egg lecithin (Co-surfactant) were selected for the preparation of SNEDDS. Tablets with high porosity suitable for loading with SNEDDS and containing the super-disintegrants, achieved complete dissolution of Pitavastatin from the tablets. In vitro release of Pitavastatin from SNEDDS and the tablets was similar (p < 0.05). Conclusion: SNEDDS of Pitavastatin is a promising approach to achieving a solid dosage form of the liquid-loaded drug delivery systems for enhancing the solubility and dissolution rate of the drug, and hence also its bioavailability.
Keywords: self-nanoemulsifying